2019
DOI: 10.1155/2019/8103812
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics in Patients with Rheumatoid Arthritis: Differences between Genders

Abstract: Objective. To compare the clinical characteristics of a group of men and women with rheumatoid arthritis (RA) and determine the differences between genders. Materials and Methods. A descriptive and comparative cross-sectional study was developed with a group of 50 men and a control group of 50 women with RA, from a rheumatology center in the city of Guayaquil, Ecuador. Data collected included clinical manifestations, comorbidities, treatment, and disease activity. Clinical and activity differences between sexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 26 publications
9
39
0
1
Order By: Relevance
“…Polyarthritis was the presenting symptom in all the cases mostly with EMS (63.3%) and deformity (16.66%), which was very similar to a study done in Kolkata, India. [ 16 ] The mean duration was 32.7 months at presentation which is in accordance with a study done in Kathmandu, Nepal. [ 17 ] The joint inflammation and muscle atrophy due to the disease reduces the range of motion of joints.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Polyarthritis was the presenting symptom in all the cases mostly with EMS (63.3%) and deformity (16.66%), which was very similar to a study done in Kolkata, India. [ 16 ] The mean duration was 32.7 months at presentation which is in accordance with a study done in Kathmandu, Nepal. [ 17 ] The joint inflammation and muscle atrophy due to the disease reduces the range of motion of joints.…”
Section: Discussionsupporting
confidence: 86%
“…[ 14 ] Females had a higher incidence than males in the study, which was in accordance with two similar studies done in India. [ 15 16 ] It was found that nearly 85% of females had an insidious onset.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that females have a more aggressive RA disease with increased activity of the disease and disability. [ 31 ] Owing to these findings, periodontitis severity in different gender among the RA and OA groups was compared in this study. No significant difference was found between the mean CAL values in males and females of both the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Aurrecoechea et al25 found that women had worse QoL than men. This is not surprising, as women tend to experience more pain,26 show higher disease activity,27 and have higher rates of disability,28 all of which influence QoL. Wallenius et al29 reported that a higher level of education was associated with better QoL, which could illustrate the role of patient knowledge and understanding about their condition in their ability to cope with it.…”
Section: Discussionmentioning
confidence: 99%